Analisis Model dan Metode Perencanaan Pendidikan dalam Perspektif Teoretis dan Implementatif di Era Digital - Yusrianti, Itel; Susanti, Eri (Indo-MathEdu Intellectuals Journal, 2025)
This study analyses educational planning models and methods from theoretical and implementative perspectives, taking into account the challenges and opportunities arising from the development of digital technology. A qualitative approach was used through a literature study, collecting data from scientific articles, books, policy reports, and official documents, which were then analysed using content analysis techniques to examine the main themes and patterns. The results of the study show that traditional planning models are still relevant, but need to be adapted to accommodate the use of real-time data, digital technology, and the dynamic needs of society. Technology-based planning methods, such as blended learning, LMS-based distance learning, and digital material development, are important strategies in the digital age. However, their implementation still faces obstacles in the form of infrastructure limitations, human resource competencies, and educational access gaps. These findings emphasise that digital transformation requires adaptive management, continuous training, and cross-sector collaboration so that technology can be effectively integrated into educational planning. Overall, this study concludes that the use of technology in educational planning and management has the potential to improve accuracy, transparency, and inclusiveness if supported by adequate infrastructure readiness and digital literacy.